PENGARUH KUALITAS PRODUK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS MAHASISWA PROGRAM STUDI MANAJEMEN - Putra Buana (LP2M Universitas Bina Bangsa, 2022)
This study aims to determine the effect of product quality and costumer satisfaction on student loyalty. This type of research is quantitative research sample of 78 students majoring in management on the campus of STIE